On Janowski Analytic p, q-Starlike Functions in Symmetric Circular Domain. (10th October 2020) - Khan, Muhammad Ghaffar; Ahmad, Bakhtiar; Frasin, Basem Aref; Abdeljawad, Thabet
Abstract : The main object of the present paper is to apply the concepts of p, q -derivative by establishing a new subclass of analytic functions connected with symmetric circular domain. Further, we investigate necessary and sufficient conditions for functions belonging to this class. Convex combination, weighted mean, arithmetic mean, growth theorem, and convolution property are also determined.